Response-mediated spatial priming despite perfectly valid target location cues and intervening response events. Issue 9 (26th November 2017) - Hilchey, Matthew D.; Rajsic, Jason; Huffman, Greg; Pratt, Jay
ABSTRACT: Attentional effects are often inferred from keypress reaction time (RT) studies when two sequentially presented stimuli, appearing at the same location, generate costs or benefits. The universality of these attentional attributions is challenged by data from perceptual discrimination tasks, which reveal that location repetition benefits and costs depend on whether a prior response repeats or switches, respectively. According to dual-stage accounts, these post-attentional effects may be abolished by making responses in between two target stimuli or by increasing target location certainty, leaving only attentional effects. Here, we test these accounts by requiring responses to stimuli in between targets and by increasing target location certainty with 100% valid location cues. Contrary to expectations, there was no discernible effect of cueing on any repetition effects, although the intervening response diminished stimulus-response repetition effects while subtly reducing location-response repetition effects. Despite this, there was little unambiguous evidence of attentional effects independent of responding. Taken together, the results further highlight the robustness of location-response repetition effects in perceptual discrimination tasks, which challenge whether there are enduring attentional effects in this paradigm.